Exploitation of Minority Community in Nasrin’s Lajja: Marxist Perspective - Shrivastwa, Bimal Kishore (Pakistan Journal of Humanities and Social Sciences, 2022)
This paper seeks to examine the terrific effects of the economic exploitation and domination of the plebeian Hindu communities by the majority of aristocratic Muslim communities in Bangladesh in Taslima Nasrin’s Lajja. The genesis of the novel lies in the demolition of the Babri Masjid in India by Hindu extremists on December 1, 1992, and its effects in Bangladesh thereafter. The destruction of the temples, burning down of shops and houses, and rape of the proletariat Hindu women clearly signify the exploitation of the proletariat by the capitalists. The research tool used to survey the issue is the Marxist theoretical perspectives elaborated by Lois Tyson and Karl Marx and Friedrich Engels. This conflict is similar to the scenario of Marxism, which deals with the conflict between the oppressed class and the oppressor. The Hindu minority community can be compared to the exploited class and the Muslim fundamentalists as the exploiters. The chief finding of the research is that the lower class Hindu women were raped, and the proletariat Hindu males were beaten; their property was destroyed or looted by the so-called Muslim capitalists, taking advantage of the weakness of the plebeians. Nasrin has portrayed the harassment, discrimination, and persecution of lower-class Hindu people by the bourgeois Muslims in Bangladesh. It is expected that readers opting to approach Nasrin from the Marxist perspective can take the paper as a reference.